Psychological Effects of Snapchat Use on Female Students of Sulaimani University - Allah, Prof.Dr. Ibrahim Saeed Fattah Allah Fattah; Ahmad, Prof. Dr. Pave Jamil (Sulaimani Journal for Humanities, 2025)
The aim of this study is to examine the psychological effects of using the Snapchat application on female students at Sulaimani University, for this purpose, female students from the Department of Media in the College of Humanities were taken as the sample population and Survey forms were distributed. The study reached several conclusions, revealing that the psychological effects of Snapchat use vary among students, and are between positive and negative. Additionally, the study recommends incorporating digital media education into the curriculum of various educational institutions such as schools and universities to help students with the knowledge to use these applications and avoid potential negative psychological effects.